2017
DOI: 10.1111/nph.14788
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 18O‐labelled water vapour on the oxygen isotope ratio of water and assimilates in plants at high humidity

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 76 publications
9
92
0
Order By: Relevance
“…This difference is larger than the range of 18 O-enrichment observed for the upper 10 cm depth of soil water under tropical humid forests (2-3 ‰; Liu et al, 2008;Stahl et al, 2013), suggesting that evaporative isotope signatures of both soils and leaf water imprinted the Globular granulate phytolith type. This is in line with recent 18 O-labelling experiment showing that the 18 O-enriched oak phloem water may exchange with xylem water under low transpiration rates (Lehmann et al, 2018).…”
Section: Imprint Of Changes In Atmospheric Rh On the 17 O-excess Of Psupporting
confidence: 77%
See 2 more Smart Citations
“…This difference is larger than the range of 18 O-enrichment observed for the upper 10 cm depth of soil water under tropical humid forests (2-3 ‰; Liu et al, 2008;Stahl et al, 2013), suggesting that evaporative isotope signatures of both soils and leaf water imprinted the Globular granulate phytolith type. This is in line with recent 18 O-labelling experiment showing that the 18 O-enriched oak phloem water may exchange with xylem water under low transpiration rates (Lehmann et al, 2018).…”
Section: Imprint Of Changes In Atmospheric Rh On the 17 O-excess Of Psupporting
confidence: 77%
“…Stem water is usually used as an analogue of soil water when modelling δ 17 O LW and δ 18 O LW (Landais et al, 2006;Li et al, 2017). However, in the stem, water in the phloem that is bidirectional (moves up and down the plant's stem) receives the contribution of evaporating leaf water, and water in the xylem that is unidirectional (moves up the plant's stem) may exchange with phloem waters (Lehmann et al, 2018). Consequently one may expect the isotope composition of stem water to be slightly different than that of soil water (Berkelhammer et al, 2013;Treydte et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the effects of labelling, δ 18 O values of leaf water and assimilates during the 9‐hr fog event were corrected for natural isotope abundances (Lehmann et al, ). Δδ18normalO=δ18Ofogδ18Oprefog, where δ 18 O fog is the isotope ratio of a sample taken during or at the conclusion of the 9‐hr labelling period and δ 18 O prefog is the isotope ratio of a sample taken before labelling start (at 08:30 a.m.).…”
Section: Methodsmentioning
confidence: 99%
“…Our understanding on how δ 18 O V signals are transferred to δ 18 O of plant organic matter and assimilates is even more limited. Research to date has demonstrated that variation in δ 18 O LW induced by step changes in δ 18 O V can be incorporated into δ 18 O of plant organic matter, and the incorporation may differ among different sugar compounds (Lehmann et al, ; Studer, Siegwolf, Leuenberger, & Abiven, ). However, it remains unclear if the observed compound‐specific pattern, with some compounds being more sensitive to water vapour‐induced δ 18 O LW variations than others, can be generalized among species and growth forms.…”
Section: Introductionmentioning
confidence: 99%